Penerapan Personal Branding “Venny Eriska” Sebagai Lifestyle Influencer dan Blogger Medan di Media Sosial Instagram - Utami, Anggun (Universitas Muhammadiyah Sumatera Utara, 2024)
Current developments in information technology, especially in social media. Paying attention to and building a good personal brand in this technological era is very important, considering the increasingly complex nature of competition. One way to show brand identity is through personal branding, which is a process for someone to manage and control other people's perceptions of the individual brand they are building. This research aims to find out how the personal branding